INFLUENCE OF KEGEL GYMNASTICS ON PRIMIGRAVIDA PREGNANCY TOWARDS THE INCIDENCE OF A PERINEAL RUPTURE IN BASIC ESSENTIAL OBSTETRIC CARE NEONATES SURAKARTA, INDONESIA - Khasanah, Umi; Yulastini, Fitria (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Kegel gymnastics can strengthen pelvic floor muscles and improve blood circulation and posture so that the perineal muscles and the perineal floor muscles become elastic. Perineal rigidity is the maternal factor which can lead to perineal rupture. Aims: The objective of the study is to determine the effect of Kegel gymnastics for primigravidas on the incidence of perinealrupture. Method: This study employed the quasi-experimental method with the control group design. Its samples were determined through the quota sampling technique. The subjects of the research were primigravidas as many as 40. They were divided equally into two groups â intervention group and control group. The data of the research was collected through observation sheet for evaluation of Kegel gymnastics for at least three weeks and pantograph sheet. They were analyzed by statistical analysis with the Chi-square formula aided with the computer program of SPSS Version 16 for Windows. Result: Only 40% mothers experienced a perineal rupture if excercised kegel gymnastics. It was significantly lower compared to their counterpart in the control group with no exercise (p-value = 0.001). Conclusion: Kegel gymnastics may lower the incidence of perineal rupture among the primigravidas.Â